Associative Processes in Intuitive Judgment - Morewedge, Carey K. (Trends Cogn Sci, 2010)
Dual-system models of reasoning attribute errors of judgment to two failures. The automatic operations of a “System 1” generate a faulty intuition, which the controlled operations of a “System 2” fail to detect and correct. We identify System 1 with the automatic operations of associative memory and draw on research in the priming paradigm to describe how it operates. We explain how three features of associative memory—associative coherence, attribute substitution, and processing fluency—give rise to major biases of intuitive judgment. Our article highlights both the ability of System 1 to create complex and skilled judgments and the role of the system as a source of judgment errors.